1982
DOI: 10.1111/j.1748-1716.1982.tb07018.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin‐induced increase in intestinal blood flow in the anesthetized rat

Abstract: Cardiac output (CO) and blood flow to major organs were investigated in pentobarbital-anesthetized rats using 85Sr and 141Ce labelled microspheres (MS) of 15 microns diameter injected into the left ventricle. Changes in organ blood flow and CO were measured after intraventricular dextran (3.4 mumol/kg/min) and intravenous neurotensin (NT) at two different rates, 2.5 nmol/kg/min and 0.125 nmol/kg/min. Dextran, known to give anaphylactoid response in rats, reduced the mean arterial pressure (MAP) from 118 +/- 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In contrast, NT produces dose-dependent increase in blood pressure in guinea-pig (Bachelard et al, 1987;Kerouac et al, 1981;Nisato et al, 1994;Rioux et al, 1982a;Rioux and Lemieux, 1992). In many studies, NT has also been reported to evoke biphasic or triphasic variations of blood pressure (Gully et al, 1996;Kaczynska and Szereda-Przestaszewska 2012;Kerouac et al, 1981Kerouac et al, , 1983Nisato et al, 1994;Oishi et al, 1981;Onarheim et al, 1982;Quirion et al, 1980d;Rioux et al, 1982aRioux et al, , 1982b.…”
Section: Blood Pressurementioning
confidence: 81%
See 1 more Smart Citation
“…In contrast, NT produces dose-dependent increase in blood pressure in guinea-pig (Bachelard et al, 1987;Kerouac et al, 1981;Nisato et al, 1994;Rioux et al, 1982a;Rioux and Lemieux, 1992). In many studies, NT has also been reported to evoke biphasic or triphasic variations of blood pressure (Gully et al, 1996;Kaczynska and Szereda-Przestaszewska 2012;Kerouac et al, 1981Kerouac et al, , 1983Nisato et al, 1994;Oishi et al, 1981;Onarheim et al, 1982;Quirion et al, 1980d;Rioux et al, 1982aRioux et al, , 1982b.…”
Section: Blood Pressurementioning
confidence: 81%
“…NT reduces gastric mucosal blood flow in human subjects (Fletcher et al, 1985), and evokes a significant dose-dependent increase in intestinal blood flow in rat (Onarheim et al, 1982), cat (Harper et al, 1984) and dog (Konturek et al, 1983). Notably, the intestinal vasodilation following systemic NT administration is induced at concentrations below those eliciting hypotension, suggesting that locally released NT could potentially act as a Schaeffer et al (1997) mediator of postprandial intestinal hyperemia (Parker et al, 1995).…”
Section: Gastrointestinal Blood Flowmentioning
confidence: 96%
“…However, administration of an NT analog to normal rats led to hypotension [759]. Consistent with this result are the observations that python NT evoked regional vasodilation [760] and that systemic administration of neurotensin to anesthetized rats induced an increase in intestinal blood flow [761].…”
Section: Neurotensinmentioning
confidence: 56%
“…CCK causes dose-dependent increases in blood pressure and, at higher doses, a generalized vasodilation [10]. Neurotensin is also known to cause vasodilation and, in addition, causes increased vascular permeability in the intestine [11]. Moreover, its systemic concentration increases after ischemia-reperfusion.…”
Section: Introductionmentioning
confidence: 98%